Meningeal carcinomatosis and spinal cord infiltration caused by a locally invasive pulmonary adenocarcinoma in a cat. Issue 2 (November 2017) - Posporis, Christoforos; Grau-Roma, Llorenç; Travetti, Olga; Oliveira, Maria; Polledo, Laura; Wessmann, Annette
Case summary: A 12-year-old domestic shorthair cat was presented with acute non-painful hindlimb proprioceptive ataxia localising to T3–L3 spinal cord segments. MRI revealed paravertebral muscular hyperintensity on T2-weighted images at the level of T7–T8 vertebrae. The cat improved on conservative management but deteriorated 3 months later. Repeated MRI showed meningeal enhancement at the same level and hyperintensity of the paravertebral musculature extending to the right thoracic wall and pleural space on short tau inversion recovery images. Thoracic CT showed mineralised lesions of the right lung, restricted pleural effusion and expansile bone lesions affecting multiple ribs. The cat had been treated for pyothorax 5 years earlier but manifested no current respiratory signs. Cerebrospinal fluid (CSF) examination showed lymphocytic pleocytosis but no neoplastic cells. Biopsy of the affected muscles and cytology of the lung and pleural lesions suggested a malignant epithelial cell tumour. Post-mortem examination confirmed a pulmonary adenocarcinoma locally infiltrating the thoracic wall, T7–T8 vertebrae and the spinal cord white matter. Meningeal carcinomatosis was detected with neoplastic cells invading the ventral median fissure of the spinal cord. No metastases were observed in other organs, indicating that neoplastic cells reached the spinal cord by direct extension. Relevance and novel information: Spinal meningeal carcinomatosis has not been reported in dogs or cats with extraneural tumours but is a well-recognised condition in humans. A metastatic cause of meningeal enhancement should be considered in patients with neurological signs of unknown origin. Imaging findings and CSF results can be non-specific.